VILLAGE GOVERNMENT MOTIVATION IN EMPOWERING VILLAGE COMMUNITIES IN VILLAGE DEVELOPMENT IN LALANG VILLAGE, MEDANG DERAS DISTRICT, BATU BARA REGENCY - Rosmaini Rosmaini; kariaman sinaga; Muzayanah Br Depari (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Rural community empowerment is a strategic instrument for participatory and sustainable village development. Village government plays a central role as the prime mover in motivating residents to engage actively in development. This study aims to analyse the form and manifestation of village government motivation in empowering communities, identify the factors influencing this motivation, and assess the implications of village government motivation on the success of village development in Lalang Village, Medang Deras Sub-district, Batu Bara Regency. The study uses a qualitative descriptive approach with a case-study method. Data were obtained through in-depth interviews, participatory observation, and documentation involving the Village Head, village officials, community leaders, and beneficiary residents. Data were analysed using the interactive model of Miles and Huberman, supported by triangulation. The findings show that the motivation of village government emerges from a combination of intrinsic and extrinsic motivation. Intrinsic motivation is reflected in the sense of responsibility, the commitment to public service, and the pride of village officials in advancing the village. Extrinsic motivation arises from policy support, social recognition, leadership of the Village Head, and the availability of work facilities. Driving factors include participatory leadership, clear task division, capacity building, and community support. Inhibiting factors include limited official competence, high administrative burden, uneven community participation, and local socio-political dynamics. Government motivation indirectly influences village development through the quality of empowerment processes, namely awareness raising, capacity strengthening, and empowerment. Strong motivation among officials promotes higher community participation, institutional consolidation, and the rise of local economic initiatives. Keywords: Village Government Motivation; Community Empowerment; Village Development; Community Participation; Rural Governance